Device Performance of Emerging Photovoltaic Materials (Version 1). Issue 11 (4th December 2020) - Almora, Osbel; Baran, Derya; Bazan, Guillermo C.; Berger, Christian; Cabrera, Carlos I.; Catchpole, Kylie R.; Erten‐Ela, Sule; Guo, Fei; Hauch, Jens; Ho‐Baillie, Anita W. Y.; Jacobsson, T. Jesper; Janssen, Rene A. J.; et al.
Abstract: Emerging photovoltaics (PVs) focus on a variety of applications complementing large scale electricity generation. Organic, dye‐sensitized, and some perovskite solar cells are considered in building integration, greenhouses, wearable, and indoor applications, thereby motivating research on flexible, transparent, semitransparent, and multi‐junction PVs. Nevertheless, it can be very time consuming to find or develop an up‐to‐date overview of the state‐of‐the‐art performance for these systems and applications. Two important resources for recording research cells efficiencies are the National Renewable Energy Laboratory chart and the efficiency tables compiled biannually by Martin Green and colleagues. Both publications provide an effective coverage over the established technologies, bridging research and industry. An alternative approach is proposed here summarizing the best reports in the diverse research subjects for emerging PVs. Best performance parameters are provided as a function of the photovoltaic bandgap energy for each technology and application, and are put into perspective using, e.g., the Shockley–Queisser limit. In all cases, the reported data correspond to published and/or properly described certified results, with enough details provided for prospective data reproduction. Additionally, the stability test energy yield is included as an analysis parameter among state‐of‐the‐art emerging PVs. Abstract : The first survey of the emerging photovoltaic reports initiative summarizes the best achievements published in academic journals in the research of emerging photovoltaic materials, e.g., organic, perovskite, and dye sensitized solar cells. The reports are presented as a function of the bandgap energy for different categories such as transparency, flexibility, and stability, and compared to the Shockley–Queisser limit.